The effects of online pilates training on cognitive functions and dual task performance in people with multiple sclerosis: A randomized controlled study - Eldemir, Kader; Eldemir, Sefa; Ozkul, Cagla; Irkec, Ceyla; Guclu-Gunduz, Arzu (Multiple sclerosis and related disorders, 2025)
•Online Pilates has positive effects on cognitive functions in PwMS.•Online Pilates is beneficial for dual-task performance during balance and mobility.•Online Pilates can be alternative for PwMS with barriers to accessing clinics. Cognitive impairments in people with multiple sclerosis (PwMS) are common and aggravate dual-task (DT) performance. This study aimed to investigate the effectiveness of online Pilates training on cognitive functions and the DT performance of balance, walking, and functional mobility in PwMS. In this randomized controlled trial, forty-six PwMS were recruited and randomly allocated into two groups. The Online Pilates group (OPG) received Pilates training via videoconferences three days per week during six weeks at home. The control group (CG) was a waitlist with no Pilates treatment. Cognitive Functions were assessed with Montreal Cognitive Asssessment (MoCA), The Trail Making Test (TMT), and The Stroop Test (ST). DT performance was assessed with mental tracking and verbal fluency during postural stability (PS), walking, and functional mobility. At the end of six weeks, the interaction effects (time × group) revealed significant differences for MoCA (p = 0.024), TMT-B (p = 0.012), ST (p ≤ 0.012), PS-with mental tracking (p = 0.004), PS-with verbal fluency (p = 0.003), cadence-with mental tracking (p = 0.048), and functional mobility-with mental tracking (p = 0.043) in favor of the OPG. Additionally, MoCA, TMT, ST, and DT performance during balance and functional mobility significantly improved in after six-week online Pilates training, but did not in CG. Pilates training via videoconference was effective in the improvement of cognitive functions and DT performance in PwMS. Online Pilates may be considered for improving cognitive impairments and DT performances in PwMS with barriers to accessing clinics. ClinicalTrials.gov: NCT06462339